Design and Analysis of Management Information System Qurban (SIMAQ) at PKPU Human Initiative, East Jakarta - Oviani Viandari; Qurrotul Aini (Applied Information System and Management (AISM), 2020)
The establishment of the Pos Keadilan Peduli Umat (PKPU) Human Initiative as one of the non-governmental institutions. Concentration on humanitarian issues should have a public service standard such as a SIM (Management Information System) the goal is to fulfill role processing needs in channel qurban with modern management where more days the number of donors is getting more increase so that requires management to improve service quality. Therefore the writer analyzed and designed the Qurban Management Information System at PKPU Jakarta East. The method used in Job Training (PKL) is Rapid Application Development (RAD) through the Requirement Planning and Workshop Design stages with modeling Unified Modeling Language (UML) so as to produce analysis and design of Information Systems Qurban Management (SIMAQ), from the results of street vendors the authors analyze and design include: integrate donor data management starting from collection transactions up to reporting on distribution or distribution of qurban animals, the author designs starting from the use case diagram that will explain the sequence of activities performed by actors and systems to achieve the system needed, such as identification of actors, identification of use cases , design of use cases and use case narratives , activity diagrams, sequence diagrams, and class diagrams . Display of the system user interface qurban management information based on the duties and authority of each actor.